Le logement comme clé pour le droit à la ville des femmes - Marie-Eve Desroches (Métropoles)
Feminists around the world are claiming their right to the city. They fight against the capitalist and patriarchal dynamics that cause significant obstacles to socio-political participation and appropriation of urban resources and opportunities. Among the wide diversity of struggles and writings using the right to the city, housing is an important point of convergence because it appears as an important prerequisite to ensure the participation and the appropriation of the city. However, most social movements and academics that are using this concept consider capitalism as the main mechanism involved in urbanization that is why the right to the city is generally considered as a class struggle. Our case study on urban feminist mobilizations for the right to housing underlies the consubstantiality of patriarchy and capitalism that impede women to appropriate housing and participate in the revitalization of their neighborhood. To consider the influence of patriarchy, the conceptualization of the right to the city must be broadened or at least adapted to integrate various approaches to justice to enable feminist claims and mobilizations.